Discourse Competence as an Essential Variable in Developing Speaking Skill of students, Grade 11 - Turayeva Zukhra (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
In this article, the development of speech competence of 11th graders the current state of process design is analyzed. The main requirements of speech competence, including not only grammatical knowledge, but the ability to effectively use language skills in real society chefs will also be considered. Integration of modern technological and educational processes, as well as special attention is paid to the need to use a differentiated approach.